Anti-Corruption initiatives: Experience of several southeast asia countries / Nurul Afzan Najid …[et al.] - Najid, Nurul Afzan; Mohd Noor, Rafizah; Yaacob, Nur Ain; Zulkifli, Nursyahida; Abdul Rahim, `Ainatul Fathiyah (Universiti Teknologi MARA Cawangan Pahang, 2020)
Corruption has a negative impact on political, social-economic, cultural development of the society. It is a fundamental social phenomenon to the governments, individuals, organizations and countries, including developed and developing countries. Transparency International highlights 3 important purposes of combating the corruptions which are: rule of law, higher life quality and conditions for societal development. As corruption is a true enemy of economic development in southeast asia countries. it is imperative for the anti-corruption measures to form the paramount part of ASEAN’s agenda to ensure future growth and prosperity. A greater effort should be called for by ASEAN leaders to put transparency and anti-corruption activities in their inter-regional ministerial agenda and the ASEAN Community Vision 2025. This is to enable the promotion of greater transparency and the fight against corruption which could help ASEAN attain a smoother and more sustainable level of political, economic, and sociocultural integration. Hence, this paper objectively focuses on identifying the best practice of anti-corruption initiatives among Asian countries. Consequently, this finding can bring positive impacts to the development of anti-corruption initiatives in Malaysia and may benefit the whole nation.